Tenacious beasts : wildlife recoveries that change how we think about animals - Preston, Christopher J. (Christopher James), 1968- (The MIT Press, 2023)
"The news about wildlife is dire--more than 900 species have been wiped off the planet since industrialization. Against this bleak backdrop, however, there are also glimmers of hope and crucial lessons to be learned from animals that have defied global trends toward extinction: bears in Italy, bison in North America, whales in the Atlantic. These populations are back from the brink, some of them in numbers unimaginable in a century. How has this happened? What shifts in thinking did it demand? In crisp, transporting prose, Christopher Preston reveals the mysteries and challenges at the heart of these resurgences. Drawing on compelling personal stories from the researchers, Indigenous people, and activists who know the creatures best, Preston weaves together a gripping narrative of how some species are taking back vital, ecological roles. Each section of the book--farms, prairies, rivers, forests, oceans--offers a philosophical shift in how humans ought to think about animals, passionately advocating for the changes in attitude necessary for wildlife recovery. Tenacious Beasts is quintessential nature writing for the Anthropocene, touching on different facets of ecological restoration from Indigenous knowledge to rewilding practices. More important, perhaps, the book offers a road map--and a measure of hope--for a future in which humans and animals can once again coexist." --